2018
DOI: 10.1155/2018/8479439
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Clove (Syzygium aromaticum) Potentiate FMSP-Nanoparticles Induced Cell Death in MCF-7 Cells

Abstract: Both nanoparticles and cloves (Syzygium aromaticum) possess anticancer properties, but they do not elicit a significant response on cancer cells when treated alone. In the present study, we have tested fluorescent magnetic submicronic polymer nanoparticles (FMSP-nanoparticles) in combination with crude clove extracts on human breast cancer cells (MCF-7) to examine whether the combination approach enhance the cancer cell death. The MCF-7 cells were treated with different concentrations (1.25 μg/mL, 12.5 μg/mL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…These results suggest that NPs selectively targeted both colon and breast cancerous cells and do not cause any harm to normal and healthy cells. There are reports of involvement of nanoparticles in cancer cell death where nuclear fragmentation and nuclear disintegration were prominent features [35,36,37,38,39,40]. We recommend that Mn 0.5 Zn 0.5 Sm x Eu x Fe 1.8−2x O 4 (0.01 ≤ x ≤ 0.05) NPs possess a selective targeting capability to cancerous cells and could be a potential candidate for cancer treatments.…”
Section: Resultsmentioning
confidence: 92%
“…These results suggest that NPs selectively targeted both colon and breast cancerous cells and do not cause any harm to normal and healthy cells. There are reports of involvement of nanoparticles in cancer cell death where nuclear fragmentation and nuclear disintegration were prominent features [35,36,37,38,39,40]. We recommend that Mn 0.5 Zn 0.5 Sm x Eu x Fe 1.8−2x O 4 (0.01 ≤ x ≤ 0.05) NPs possess a selective targeting capability to cancerous cells and could be a potential candidate for cancer treatments.…”
Section: Resultsmentioning
confidence: 92%
“…In another study, clove extract has increased cytotoxic effects of gemcitabine on Hela cells [ 37 ]. Clove extracts mediated FMSP-nanoparticles have led to cancer cells death in MCF7 breast cancer cells [ 54 ]. Syzygium aromaticum has increased the cytotoxicity of tamoxifen against MCF-7 at low concentration of the drug, but it has been a strong antagonistic effect at high concentration [ 3 ].…”
Section: Main Textmentioning
confidence: 99%
“… Khan et al (2018) tested fluorescent magnetic submicronic polymer nanoparticles (FMSP-nanoparticles) alone (1.25, 12.5, 50, 75, and 100 μ g/ml) and combined with crude clove extracts (50 μ g/ml) on human breast cancer cells (MCF-7) for 24 and 48 h, using Trypan Blue, 4′,6-diamidino-2-phenylindole (DAPI) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. They showed that when treated with FMSP-nanoparticles alone, cancer cell viability was decreased to 55.40%, but decreased drastically to 8.50% when treated with combination of FMSP-nanoparticles and crude clove extracts.…”
Section: Methodsmentioning
confidence: 99%